Analisis Keefektifan Media Pembelajaran Mobuya Dalam Meningkatkan Pemahaman Keragaman Budaya Pada Siswa - Yunita, Tisa; Yunita Yasmin Istiqomah; Yona Wahyuningsih (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
Cultural diversity is one of the unique things that exist on this earth with various ethnic groups around the world, as well as the cultural diversity of Indonesia. Therefore, students must be familiar with the various cultural diversity that exists in Indonesia, especially those in the surrounding environment so that students have a sense of love and a sense of belonging to the diversity that exists in the surrounding environment regarding the existing diversity. This study uses a qualitative method. The results of this study aim to assist students in understanding the material on cultural diversity in high grades. The era is increasingly advanced in technology, so the learning tools used are also developing, adjusting the use of technology in learning media, so as not to foster a sense of boredom, and monotony in the classroom during the learning process.